Strategic Sustainability Action Plan at Unicamp - Dalbelo, Thalita dos Santos; Earp, Henrique N. Sa; Vieira, Fernando Cesar; dos Santos, Filipe Vieira Lima; Romero, Gabriela Marques; Niro, Glauco; Braga, Vanderlei; Chinelato, William; Albieri, Marcelo de Campos Garcia; Campagnoli, Renato (Universitas Diponegoro, 2025)
The Strategic Sustainability Action Plan (PAESUS) at Universidade Estadual de Campinas (Unicamp) ensures a structured and predictable approach to sustainability investments, in line with the university's 2021-2025 Strategic Plan and the Sustainable Development Goals (SDGs). The initiative integrates sustainability into academic, operational, and governance practices, promoting long-term environmental impact. In its Year Zero, PAESUS implemented pilot projects across Unicamp’s campuses, focusing on energy efficiency, water conservation, waste management, and climate resilience. In 2024, the first public call for projects attracted 17 proposals, with 10 selected for development in 2025, based on a prioritization matrix evaluating impact and feasibility. The program secured R3 million in additional and immediate investments, reinforcing initiatives in climate action, sustainable mobility, and resource optimization. With integrated governance and interdisciplinary collaboration, PAESUS fosters innovation and strengthens Unicamp’s sustainable management culture. Progress is monitored using global sustainability indicators, such as UI GreenMetric and THE Impact, ensuring accountability and continuous improvement. By advancing strategic sustainability actions, PAESUS positions Unicamp as a leader in sustainable development within higher education, offering a model for other institutions to follow.